(untitled) (International Journal of Engineering and Computer Science, 2024)
In the era of globalization and technological advancements, supply chain optimization has emerged as a critical driver of success for the manufacturing industry. Manufacturers face persistent challenges such as demand volatility, supply disruptions, inefficient resource utilization, and increasing pressure to reduce costs while maintaining high levels of customer satisfaction. Oracle NetSuite, a cloud-based Enterprise Resource Planning (ERP) solution, provides a robust framework to address these challenges by integrating supply chain processes, automating workflows, and delivering actionable insights through real-time data analytics. This paper investigates the potential of Oracle NetSuite to revolutionize supply chain management in manufacturing. By exploring NetSuite’s core functionalities—such as demand planning, procurement automation, inventory management, and global supply chain integration—the study highlights its ability to enhance operational efficiency, improve decision-making, and foster collaboration among internal and external stakeholders. The paper further provides a detailed literature review that contextualizes the role of ERP systems in supply chain optimization and examines the specific advantages of cloud-based platforms like NetSuite. A case study of a mid-sized electronics manufacturer demonstrates the practical application of NetSuite, showcasing improvements in inventory management, supplier coordination, and cost savings. The findings illustrate how leveraging NetSuite can lead to increased agility, scalability, and resilience in supply chain operations. As manufacturing organizations navigate an increasingly complex and dynamic global market, this study underscores the importance of adopting integrated digital solutions like Oracle NetSuite to remain competitive. By aligning technological capabilities with strategic supply chain goals, manufacturers can achieve sustainable growth and operational excellence.